National identity as a communication framework in advertising: Sounds, images and tastes of the past - Ocokoljić Marija (Marketing (Beograd. 1991))
The primary questions addressed in the research conducted as a qualitative content analysis were the communication framing of national identity in advertising in the Republic of Serbia. The visual, verbal, and audio elements of advertisements were observed as symbols, individually and in their interrelationships, as a cohesive narrative. The aim was to understand how national identity is adapted for commercial purposes and represented in advertising. The study explored how images, messages, sounds, and concepts are treated, and how they invite viewers to perceive national identity. Several specific symbols were highlighted. Visually, in addition to official symbols (the flag, coat of arms), food is the most prominent in presenting national identity. It is shown individually, as a particular authentic food product, or conceptually, as a meal around which people gather. Among the carriers of the narrative about national identity, sound also stands out. In most ads, music and sound effects have a distinctly ethnic character. The past has been identified as perhaps the most complex symbol of national identity. It runs through almost all narratives, within which creative treatments of the past, the selection of historical periods, and attitudes towards tradition as an aspect of the past are highlighted.